Analisis TPM pada Mesin Press Fine Blanking 1100 Ton dengan Metode OEE di Perusahaan Manufacturing Press Part - Muhammad Johan Rifa’i; Bayu Wiro Karuniawan; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
In East Java there is one company that is engaged in Stamping Press (Precision StampingParts and Fine Forming Part) which supplies several automotive manufacturing industries inIndonesia. In this company has a 1100 Ton Fine Blanking machine. The machine is still experiencinga lot of breakdown so that in this research will look for factors that affect the time of breakdown andis expected to increase the productivity of production activities. This research uses several methodsnamely OEE, RCA, and FMEA. The measurement of Overall Equipment Effectiveness (OEE) valuewill be used as the basis for improvement efforts and increase the effectiveness and productivity of the1100 Ton Fine Blanking machine. RCA is used to obtain a cause that greatly affects the decline inOEE values. While FMEA to prioritize the factors that require immediate improvement. By collectingrelated and calculated data, the OEE value is 48%. The value is not in accordance with the idealOEE standard value. Therefore a causal analysis is done and the results obtained is that dies problemis the most influencing in the decline of OEE values. One of the problems that often arise refers toRCA and FMEA is the occurrence of chipped on the main punch caused by the deformation of thematerial. So we get alternative solution to handle it by way of coating on main punch or replacematerial with higher grade.